EXAMINING ACCESS TO FINANCIAL RESOURCES FOR SMALL AND MEDIUM ENTERPRISES (SMES) IN ALGERIA: A COMPREHENSIVE ANALYSIS BEYOND WORLD BANK METRICS - HANI, Lamine; GANA, Brahim (The journal of contemporary issues in business and government, 2024)
Like many other countries throughout the world, Algeria's economy has suffered from the erratic price of oil during the past decade. Algeria's government has made great efforts in spite of these obstacles to address societal demands and economic imbalances. SMEs have become increasingly important in today's economy, playing a significant role in areas such as job creation, sustainable development, and the provision of public services. Many of Algeria's small and medium-sized enterprises (SMEs) have a low capital intensity, giving them more leeway to adapt to shifting market conditions. In 2017, the country hosted 1,035,891 micro-enterprises, totaling 97.7% of the SME sector, illustrating the prominence of SMEs in the private sector at 99.98%. Over 2.6 million jobs were directly or indirectly created by these businesses, illustrating the critical role they play in the labour economy. Further demonstrating their relevance is the purposeful concentration of SMEs in coastal locations, where they have easier access to ports and a more concentrated consumer base. Algerian small and medium-sized enterprises (SMEs) rely on self-financing rather than bank loans, as shown by the country's last national census. While government grants do help finance investments, their effect on new and growing businesses is minimal. The current economic climate makes it difficult for SMEs to secure sufficient funding, especially the latter. Financing for economic operations is mostly provided by commercial banks in Algeria, whereas stock markets have little sway, and only 2% of SMEs rely on bank loans. In conclusion, SMEs retain a crucial place in Algeria's economic framework, contributing significantly to employment and overall economic expansion. However, their path is hampered by difficulties in securing funding. Because SMEs in Algeria rely primarily on self-funding, minimally on government subsidies, and rarely on stock markets, targeted actions are essential for addressing financial shortfalls and establishing an environment suitable for sustainable growth.